Restoration of renal TIMP3 levels via genetics and pharmacological approach prevents experimental diabetic nephropathy. Issue 2 (4th February 2021) - Casagrande, Viviana; Iuliani, Giulia; Menini, Stefano; Pugliese, Giuseppe; Federici, Massimo; Menghini, Rossella
Abstract: Background: Diabetic nephropathy (DN), one of the major complications of diabetes, is characterized by albuminuria, glomerulosclerosis, and progressive loss of renal function. Loss of TIMP3, an Extracellular Matrix bound protein affecting both inflammation and fibrosis, is a hallmark of DN in human subjects and mouse models. Methods: This study was designed to provide evidences that the modulation of the system involving TIMP3 and its target A Disintegrin And Metalloproteinase 17 (ADAM17), may rescue kidney pathology in diabetic mice. Mice with cell‐targeted overexpression of TIMP3 in myeloid cells (MacT3), podocyte‐specific ADAM17 knockout mice (∆PodA17), and DBA/2J mice, were rendered diabetic at 8 weeks of age with a low‐dose streptozotocin protocol. DBA/2J mice were administered new peptides based on the human TIMP3 N‐terminal domain, specifically conjugated with G3C12, a carrier peptide highly selective and efficient for transport to the kidney. Twelve weeks after Streptozotocin injections, 24‐hour albuminuria was determined by ELISA, kidney morphometry was analyzed by periodic acid‐shift staining, and Real Time‐PCR and western blot analysis were performed on mRNA and protein extracted from kidney cortex. Results: Our results showed that both genetic modifications and peptides treatment positively affect renal function and structure in diabetic mice, as indicated by a significant and consistent decline in albuminuria along with reduction in glomerular lesions, as indicated by reduced mesangial expansion and glomerular hypertrophy, decreased deposition of extracellular matrix in the mesangium, diminished protein expression of the NADPH oxidases 4 (NOX4), and the improvement of podocyte structural markers such as WT1, nephrin, and podocin. Moreover, the positive effects were exerted through a mechanism independent from glycemic control. Conclusions: In diabetic mice the targeting of TIMP3 system improved kidney structure and function, representing a valid approach to develop new avenues to treat this severe complication of diabetes. Abstract : Loss of TIMP3 contributes to the onset and progression of diabetic nephropathy in human and mouse. Strategies aimed to increase TIMP3 activity in the diabetic kidney positively affect renal structure and function. Exogenous TIMP3 peptides, specifically targeted to the kidney, may represent a therapeutic approach for the treatment of diabetic nephropathy.